Method for preparing porous reticular bio-based sponge by regenerating waste polyurethane foam

Through the use of biological alcohol dissolutions and the use of additives, the abandoned polyurethane foam is converted into a porous mesh mesh biological sponge, solving the problem of difficulty recycling and using polyurethane foam waste, and realizing the high -value utilization of resources and the green of the polyurethane industry. Sustainable development.

CN119331196AActive Publication Date: 2025-01-21ZHENGZHOU UNIV +1

Patent Information

Application Number
CN202411497474.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-21
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

Polyurethane foam waste is difficult to recycle, resulting in waste of resources and environmental threats.

Method used

The biological alcohol dissolving agent and auxiliary agent are used to convert the abandoned polyurethane foam into a porous mesh mesh bioprotic sponge through the alcohol solution. This method includes the preparation of degradation liquid, the preparation of biological alcohol, and the preparation of mesh biology sponge.

Benefits of technology

The high -value application of abandoned polyurethane foam is realized, the waste of resources has been reduced, the green and sustainable development of the polyurethane industry has been promoted, and a porous mesh biological sponge with unique structure and performance is prepared.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331196A_ABST
    Figure CN119331196A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of polyurethane foam recovery, and particularly relates to a method for preparing porous reticular bio-based sponge by regenerating waste polyurethane foam, which comprises the following steps: firstly, crushing waste soft polyurethane foam into a specific size; then reacting the compounded alcoholysis agent, the catalyst A and the waste polyurethane foam in a reaction kettle in proportion to obtain degradation liquid; reacting the degradation liquid, an auxiliary agent and a catalyst B under specific conditions to obtain bio-based polyol; finally, the bio-based polyol and other raw materials are mixed and foamed, free forming is conducted at a certain temperature, and the bio-based polyurethane foam is obtained, the problem that polyurethane foam waste is difficult to recycle is effectively solved, resource reutilization is achieved, and resource waste and environmental threat are reduced. By adopting the combination of the relatively cheap alcoholysis agent and catalyst, the production cost is reduced, and the method is more environment-friendly and energy-saving. The prepared porous reticular bio-based sponge has unique structure and performance, can be applied to multiple fields, and has high application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyurethane foam recycling, and in particular relates to a method for preparing a porous mesh bio-based sponge by regenerating waste polyurethane foam. Background Art

[0002] As an organic synthetic material with extremely wide applications, polyurethane can be used in chemical production to produce products with different performances and appearances by changing the types and ratios of polyether polyols and polyisocyanates and adopting various production processes. With its excellent performance, polyurethane materials are widely used in many fields and have become one of the fastest-growing synthetic materials in recent years. With the annual output of polyurethane foam increasing year by year, petroleum-based polyurethane foam consumes a large amount of petroleum resources, the reaction temperature is as high as 130 °C, and the increase in waste products brings severe challenges. Polyurethane is polymerized by isocyanate and polyol, which is difficult to recycle and reuse by conventional means, resulting in the difficult-to-degrade polyurethane foam waste can only be treated as garbage, causing resource waste and environmental threats. Therefore, the development of green and widely applicable degradation agent degradation polyurethane foam recovery technology has become a major research topic with innovative significance in the field of polyurethane. At present, chemical recovery methods include hydrolysis, pyrolysis, alcoholysis, etc. Although the pyrolysis and hydrolysis methods are relatively simple to operate, they require higher temperatures and pressures and consume more energy. Alcoholysis is relatively greener and is one of the most promising recovery methods in chemical methods.

[0003] However, the current alcoholysis method mostly uses petroleum-based polyols to prepare polyurethane products. Petroleum-based polyols are non-renewable resources, and the high-value application of waste polyurethane foam is still not sufficient. Therefore, it is of great significance to achieve high-value application of waste polyurethane foam and green and sustainable development of the polyurethane industry. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a porous mesh bio-based sponge by regenerating waste polyurethane foam, aiming to solve the problems of difficulty in recycling polyurethane foam waste, waste of resources and environmental threats, while achieving high-value application of waste polyurethane foam and green and sustainable development of the polyurethane industry.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is: A method for preparing a porous mesh bio-based sponge by regenerating waste polyurethane foam, comprising the following steps: S1. Preparation of degradation liquid: alcoholysis agent, catalyst A, and polyurethane foam are mixed in a mass ratio of 100:0.5~3:20~80, placed in a stainless steel reactor, preheated to 90~160 ℃ at a speed of 200~500 rpm, reacted for 120~300 min, and kept warm at 30~60 ℃ for 10~20 min to obtain a degradation liquid, which contains hydroxyl, ester, tetrafluoroborate, butoxy, and silicate sheets. Hydroxyl and ester groups can promote the transesterification reaction of polyurethane foam, and bioethanol is gasified at high temperature, which helps to promote the breaking of urea bonds in polyurethane foam and prevent the polyurethane foam from coking during the degradation process; S2. Preparation of bio-based polyols: adding the degradation solution, additives and catalyst B prepared in step S1 to a stainless steel reactor in a mass ratio of 100:100-300:1-5, reacting at 150-210°C for 180-480 min at a speed of 200-500 rpm to obtain bio-based polyols; S3. Preparation of a reticulated bio-based sponge: The bio-based polyol, catalyst, silicone oil L580, foaming agent, pore-opening agent, and isocyanate prepared in step S2 are mixed in a mass ratio of 100:0.1~0.6:3~5:2~10:0.2~2:90~150, and then mechanically stirred and blended for foaming, and then placed at 0~25°C for free forming to obtain a bio-based polyurethane foam, i.e., a reticulated bio-based sponge. The present invention forms a regenerated cross-linked polyol by alcoholyzing waste polyurethane foam to form a long-chain polyether compound and grafting it with ricinoleic acid, etc., and then prepares a reticulated bio-based sponge. The reticulated bio-based sponge can not only provide a good buffering effect, but also be widely used in packaging, furniture, car seats and other fields, provide a comfortable use experience, and also have good filtering performance, can filter particulate matter and pollutants in the air, and keep the indoor air fresh. The reticulated bio-based sponge can not only realize the high-value application of waste polyurethane foam, but also promote the green development of the environment.

[0006] Furthermore, the polyurethane foam in step S1 is waste soft polyurethane foam and needs to be crushed to 1-5 cm before use.

[0007] Furthermore, in step S1, the alcoholysis agent is compounded from the following raw materials in mass percentage: 10-25% bioethanol, 35-50% crude glycerol, 7-15% furfuryl alcohol, 15-25% 1,4-butanediol, and 8-20% polylactic acid; the compounded alcoholysis agent can promote transesterification and urea bond cleavage reactions with the carbamate groups in the polyurethane foam, and at the same time regulate the molecular weight and viscosity of the alcoholysis product, thereby improving the performance of the alcoholysis product. Because bioethanol can form hydrogen bonds and other interactions with crude glycerol and furfuryl alcohol, the polarity of the entire alcoholysis system is enhanced, thereby improving the solubility of polyurethane foam. At the same time, the molecular chain of polylactic acid can also be entangled with the alcoholysis product or form a copolymer, thereby improving the structure and performance of the product.

[0008] Furthermore, the catalyst A is at least one of dimethyl bismuth, zinc acetate, 9-mesityl acridine, tetrabutyl titanate, titanium dioxide, antimony trioxide, molybdenum trioxide, and iron-based montmorillonite.

[0009] Furthermore, the auxiliary agent in step S2 is one of oleic acid, linoleic acid, ricinoleic acid and linolenic acid; and the catalyst B is one of potassium hydroxide, sodium hydroxide, sodium ethoxide and potassium ethoxide.

[0010] Furthermore, the catalyst in step S3 is a delayed amine catalyst A300 and stannous octoate T9, and the mass ratio of the two is 1:1-3; the isocyanate is one of toluene diisocyanate TDI and polyphenyl polymethylene polyisocyanate PMDI.

[0011] The present invention has the advantages that: 1. The present invention effectively solves the problem that polyurethane foam waste is difficult to recycle. By using bio-based alcoholysis agents and additives, waste sofa soft polyurethane foam is converted into valuable products, thus achieving resource recycling, reducing resource waste, and promoting the polyurethane industry to move towards green and sustainable development. 2. This method uses a relatively cheap alcoholysis agent and catalyst combination, which reduces production costs. Compared with thermal decomposition and hydrolysis, alcoholysis consumes less energy, is more environmentally friendly and energy-saving, and controls the reaction temperature and pressure relatively low during the preparation process, which reduces the demand for energy and meets the requirements of sustainable development; 3. The present invention proposes for the first time to use waste polyurethane foam as raw material, and to use alcoholysis method to achieve resource recycling through a relatively cheap alcoholysis agent and catalyst combination at a relatively low reaction temperature and pressure, thereby reducing dependence on non-renewable petroleum resources and waste emissions, being more environmentally friendly and energy-saving. The prepared sponge has a unique structure and performance, low density, high porosity, high tear strength, and a pore size comparable to that of commercial petroleum-based foams, and has high application value and stable and reliable performance; 4. The porous mesh bio-based sponge prepared by the method of the present invention has a unique structure and performance, and can be applied to filter materials, sound-absorbing materials, cleaning products and other fields, and has high application value. The reaction conditions and raw material ratios of each step are precisely controlled to ensure stable product performance and reliable quality.

[0012] Instruction Manual Figure 1 This is an optical image of the reticulated polyurethane foam prepared in Example 1 of the present invention.

[0013] Figure 2 FTIR spectra of Example 1 and Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0014] Example 1 The waste polyurethane foam was crushed to 1-3 cm, and the alcoholysis agent (bioethanol: crude glycerol: furfuryl alcohol: 1,4-butanediol: polylactic acid mass ratio of 20:40:10:15:15), catalyst A (zinc acetate: tetrabutyl titanate mass ratio of 1:1) and waste polyurethane foam were mixed in a stainless steel reactor at a mass ratio of 100:1:50, and the speed was controlled to be 300 rpm and heated to 120 ℃, reacted for 240 min, cooled to 40 ℃, and kept warm for 10 min to obtain the degradation solution. The degradation solution: auxiliary agent (oleic acid): catalyst B (sodium hydroxide) were added to the stainless steel reactor at a mass ratio of 100:200:3 and reacted at 200 ℃ for 360 min to obtain the bio-based polyol. The molecular weight of the bio-based polyol was 4520, the hydroxyl value was 80 mg KOH / g, and the viscosity was 500 mPa·s. Bio-based polyol: catalyst: silicone oil L580: foaming agent: cell opener: isocyanate were mixed in a mass ratio of 100:0.3:3:3:0.5:100, and the mixture was blended and foamed by mechanical stirring. After stirring for 20 seconds, the mixture was placed at 0-25°C for free forming to obtain a porous network bio-based polyurethane sponge, which served as a filter material. After being placed for 72 hours, the density of the porous network bio-based polyurethane foam was measured to be 30 kg / m 3 , porosity is 98%, pore size is 80 PPI, and tear strength is 15 N / cm.

[0015] Example 2 The waste polyurethane foam was crushed to 2-4 cm, and the alcoholysis agent (bioethanol: crude glycerol: furfuryl alcohol: 1,4-butanediol: polylactic acid mass ratio of 15:45:12:18:10), catalyst A (dimethyl bismuth: titanium dioxide mass ratio of 2:1) and waste polyurethane foam were mixed in a stainless steel reactor at a mass ratio of 100:2:60, and the speed was controlled at 400 rpm, heated to 140℃, reacted for 200 min, then cooled to 50℃, and kept warm for 15 min to obtain the degradation solution. The degradation solution, auxiliary agent (linoleic acid) and catalyst B (sodium ethoxide) were added to the stainless steel reactor at a mass ratio of 100:250:4, and reacted at 190℃ for 400 min to obtain bio-based polyols. The molecular weight of the bio-based polyol was 4800, the hydroxyl value was 75 mg KOH / g, and the viscosity was 550 mPa·s. The bio-based polyol, catalyst (the mass ratio of delayed amine catalyst A300 and stannous octoate T9 was 1:2), silicone oil L580, foaming agent, pore opening agent, and isocyanate were mixed in a mass ratio of 100:0.4:4:4:0.8:120, and the mixture was blended and foamed by mechanical stirring. After stirring for 25 s, the mixture was placed at 0~25 ℃ for free forming to obtain a porous mesh bio-based polyurethane sponge, which served as a filter material. After being placed for 72 hours, the density of the porous mesh bio-based polyurethane sponge was measured to be 28 kg / m³, the porosity was 97%, the pore size was 86 PPI, and the tear strength was 13 N / cm.

[0016] Example 3 The waste polyurethane foam was crushed to 3-5 cm, and the alcoholysis agent (bioethanol: crude glycerol: furfuryl alcohol: 1,4-butanediol: polylactic acid mass ratio of 18:42:11:16:13), catalyst A (9-mesitylene acridine: antimony trioxide mass ratio of 1:2) and waste polyurethane foam were mixed into a stainless steel reactor at a mass ratio of 100:1.5:70. The speed was controlled at 350 rpm, heated to 130 ℃, reacted for 220 min, then cooled to 45 ℃, and kept warm for 12 min to obtain the degradation liquid. The degradation liquid, auxiliary agent (ricinoleic acid), and catalyst B (potassium ethanol) were added to the stainless steel reactor at a mass ratio of 100:220:3.5, and reacted at 185 ℃ for 380 min to obtain bio-based polyols. The molecular weight of the bio-based polyols was 4650, the hydroxyl value was 78 mg KOH / g, and the viscosity was 520 mPa·s. Polyol, catalyst (delayed amine catalyst A300 and stannous octoate T9 mass ratio of 1:2.5), silicone oil L580, foaming agent, pore opening agent, isocyanate were mixed in a mass ratio of 100:0.5:3.5:5:1:110, and mechanical stirring was used for blending and foaming. After stirring for 30 seconds, the porous mesh bio-based polyurethane sponge was placed at 0-25 °C for free forming to obtain a porous mesh bio-based polyurethane sponge as a filter material. After 72 hours of placement, the density of the porous mesh bio-based polyurethane sponge was measured to be 29 kg / m³, the porosity was 96%, the pore size was 89 PPI, and the tear strength was 12 N / cm.

[0017] Example 4 The waste polyurethane foam was crushed to 1~4 cm, and the alcoholysis agent (bioethanol: crude glycerol: furfuryl alcohol: 1,4-butanediol: polylactic acid mass ratio of 16:44:13:17:10), catalyst A (iron-based montmorillonite: molybdenum trioxide mass ratio of 3:1) and waste polyurethane foam were mixed into a stainless steel reactor at a mass ratio of 100:2.5:75. The speed was controlled at 450 rpm, heated to 150 ℃, reacted for 180 min, then cooled to 55 ℃, and kept warm for 18 min to obtain the degradation liquid. The degradation liquid, auxiliary agent (linolenic acid), and catalyst B (sodium hydroxide) were added to the stainless steel reactor at a mass ratio of 100:280:4.5, and reacted at 205 ℃ for 420 min to obtain bio-based polyols. The molecular weight of the bio-based polyols was 4900, the hydroxyl value was 72 mg KOH / g, and the viscosity was 580mPa·s. Bio-based polyol, catalyst (delayed amine catalyst A300 and stannous octoate T9 mass ratio of 1:1.5), silicone oil L580, foaming agent, pore opening agent, isocyanate were mixed in a mass ratio of 100:0.2:4.5:6:1.2:130, and mechanical stirring was used for blending and foaming. After stirring for 28 seconds, the porous mesh bio-based polyurethane sponge was placed at 0-25 °C for free forming to obtain a porous mesh bio-based polyurethane sponge as a filter material. After being placed for 72 hours, the density of the porous mesh bio-based polyurethane sponge was measured to be 27 kg / m³, the porosity was 98%, the pore size was 102 PPI, and the tear strength was 10 N / cm.

[0018] Example 5 The waste polyurethane foam was crushed to 2-5 cm, and the alcoholysis agent (bioethanol: crude glycerol: furfuryl alcohol: 1,4-butanediol: polylactic acid mass ratio of 17:43:12:15:13), catalyst A (tetrabutyl titanate: antimony trioxide mass ratio of 2:1) and waste polyurethane foam were mixed into a stainless steel reactor at a mass ratio of 100:1.8:65. The speed was controlled at 380 rpm, heated to 135 ℃, reacted for 210 min, then cooled to 48 ℃, and kept warm for 16 min to obtain the degradation liquid. The degradation liquid, auxiliary agent (oleic acid), and catalyst B (potassium ethanol) were added to the stainless steel reactor at a mass ratio of 100:240:3.8, and reacted at 195 ℃ for 390 min to obtain bio-based polyols. The molecular weight of the bio-based polyols was 4700, the hydroxyl value was 76 mg KOH / g, and the viscosity was 540 mPa·s. Bio-based polyol, catalyst (delayed amine catalyst A300 and stannous octoate T9 mass ratio of 1:2.2), silicone oil L580, foaming agent, pore opening agent, isocyanate were mixed in a mass ratio of 100:0.35:4:4.5:0.9:115, and mechanical stirring was used for blending and foaming. After stirring for 22 seconds, the porous mesh bio-based polyurethane sponge was placed at 0-25 °C for free forming to obtain a porous mesh bio-based polyurethane sponge as a filter material. After being placed for 72 hours, the density of the porous mesh bio-based polyurethane sponge was measured to be 28.5 kg / m³, the porosity was 99%, the pore size was 103 PPI, and the tear strength was 9 N / cm.

[0019] Comparative Example 1 The waste polyurethane foam was crushed to the same size as in Example 1, and a single bioethanol was used as an alcoholysis agent. The alcoholysis agent, catalyst A (the same as in Example 1) and waste polyurethane foam were mixed in a stainless steel reactor at a mass ratio of 100:1:50, and the same rotation speed, temperature and reaction time were controlled to obtain a degradation solution. There was some undegraded waste polyurethane foam in the degradation solution, and the subsequent steps were exactly the same as in Example 1. After being placed for 72 hours, the density of the porous mesh bio-based polyurethane sponge was measured to be 45 kg / m³, the porosity was 42%, the pore size was 40PPI, and the tear strength was 6 N / cm.

[0020] Comparative Example 2 The waste polyurethane foam was crushed to the same size as in Example 1, and a single 1,4-butanediol was used as an alcoholysis agent. The alcoholysis agent, catalyst A (the same as in Example 1) and the waste polyurethane foam were mixed in a stainless steel reactor at a mass ratio of 100:1:50, and the rotation speed, temperature and reaction time were controlled to be the same. Since the foam did not dissolve, the foam came into contact with the wall of the reactor during the stirring process, resulting in carbonization of the foam, and the subsequent foaming step could not be carried out.

[0021] Comparative Example 3 The waste polyurethane foam was crushed to the same size as in Example 1, and a single furfuryl alcohol was used as an alcoholysis agent. The alcoholysis agent, catalyst A (the same as in Example 1) and the waste polyurethane foam were mixed in a stainless steel reactor at a mass ratio of 100:1:50. The rotation speed, temperature and reaction time were controlled to be the same. The foam was not completely dissolved. Since the foam was not dissolved, the foam came into contact with the wall of the reactor during the stirring process, resulting in carbonization of the foam, and the subsequent foaming step could not be carried out.

[0022] Comparative Example 4 The waste polyurethane foam was crushed to the same size as in Example 1, and a single crude glycerol was used as an alcoholysis agent. The alcoholysis agent, catalyst A (the same as in Example 1) and waste polyurethane foam were mixed in a stainless steel reactor at a mass ratio of 100:1:50, and the same rotation speed, temperature and reaction time were controlled to obtain a degradation solution. There was some undegraded waste polyurethane foam in the degradation solution, and the subsequent steps were exactly the same as in Example 1. After being placed for 72 hours, the density of the porous mesh bio-based polyurethane sponge was measured to be 68 kg / m³, the porosity was 23%, the pore size was 31PPI, and the tear strength was 5 N / cm.

[0023] Comparative Example 5 The waste polyurethane foam was crushed to the same size as in Example 1, and a single polylactic acid was used as an alcoholysis agent. The alcoholysis agent, catalyst A (the same as in Example 1) and waste polyurethane foam were mixed in a stainless steel reactor at a mass ratio of 100:1:50, and the rotation speed, temperature and reaction time were controlled to be the same. The foam did not dissolve and coked. The subsequent foaming step could not be performed.

[0024] Comparative Example 6 A reticulated polyurethane foam sold on the market uses petroleum-based polyol as a foaming raw material in its production process. The performance of the foam was tested according to the same test method as in Example 1. The test results show that the density of the petroleum-based reticulated foam is 35 kg / m³, the porosity is 96%, the pore size is 43 PPI, and the tear strength is 10 N / cm.

[0025] Test example The test performance result lists of Examples 1-5 of the present invention and Comparative Examples 1-6 are compared and analyzed, and the test results are shown in Table 1.

[0026] Table 1 Comparison of performance of reticulated polyurethane sponge As shown in the table above, the alcoholysis agent used in Examples 1-5 of the present invention can alcoholyze polyurethane soft foam, and the obtained bio-based polyol can be used to prepare a mesh polyurethane sponge for filter materials. Because the bio-based polyol obtained by using the compound alcoholysis agent to degrade waste polyurethane foam has a lower viscosity and a molecular weight greater than that of commercial petroleum-based polyols, the density of the obtained bio-based polyurethane sponge is as low as 30 kg / m³, the porosity is as high as more than 95%, and the tear strength is also greater than 9N / cm. The porosity and pore size of the bio-based polyurethane sponge are comparable to those of commercial petroleum-based foams. Comparative Examples 2, 3, and 5 show that single 1,4-butanediol, furfuryl alcohol, and polylactic acid as alcoholysis agents cannot completely alcoholyze polyurethane foam, indicating that these single alcoholysis agents are limited. Single crude glycerol and bioethanol can alcoholyze polyurethane foam, but the reticulated polyurethane foam prepared with these bio-based polyols has poor performance in filter materials, with a porosity of less than 50%, a pore size of less than 50 PPI, and a tear strength as low as 5 N / cm. The overall performance is much different from that of the reticulated polyurethane foam prepared with a composite alcoholysis agent.

[0027] The product structure test prepared by the present invention shows that Figure 1 It can be observed that the regenerated reticulated polyurethane sponge has a three-dimensional open-pore structure. Figure 2 FTIR spectra of Example 1 and Comparative Example 4 of the present invention. -1 In the range of 3300 cm-1, symmetric and asymmetric stretching vibrations were observed, which are related to the vibrations of methylene and methyl groups in the polymer backbone. -1 The stretching vibration peaks of the polyols indicate that the OH groups in the regenerated polyols reacted with PMDI during the polymerization process to form NH groups.

[0028] In summary, bioethanol can form hydrogen bond interactions with alcoholysis agents such as crude glycerol and furfuryl alcohol, enhance the polarity of the entire alcoholysis system, and improve the solubility of polyurethane foam. At the same time, the molecular chain of polylactic acid can be entangled with the alcoholysis product, thereby improving the structure and performance of the product. The compound alcoholysis agent can not only alcoholyze polyurethane foam, but also the performance of the reticulated polyurethane sponge prepared with the generated bio-based polyol in the filter material is better than that of the polyurethane sponge prepared by a single alcoholysis agent and commercial petroleum-based foam.

Claims

1. A method for preparing a porous mesh bio-based sponge by regenerating waste polyurethane foam, characterized in that: The following steps are involved: S1. Preparation of degradation solution: alcoholysis agent, catalyst A and polyurethane foam are mixed in a mass ratio of 100:0.5~3:20~80, placed in a stainless steel reactor, preheated to 90~160°C at a speed of 200~500 rpm, reacted for 120~300 min, and kept warm at 30~60°C for 10~20 min to obtain a degradation solution; S2. Preparation of bio-based polyols: adding the degradation solution, additives and catalyst B prepared in step S1 to a stainless steel reactor in a mass ratio of 100:100-300:1-5, reacting at 150-210 °C for 180-480 min at a speed of 200-500 rpm to obtain bio-based polyols; S3. Preparation of a reticulated bio-based sponge: The bio-based polyol, catalyst, silicone oil L580, foaming agent, pore opening agent and isocyanate prepared in step S2 are mixed in a mass ratio of 100:0.1~0.6:3~5:2~10:0.2~2:90~150, blended and foamed by mechanical stirring, and then placed at 0~25°C for free forming to obtain a bio-based polyurethane foam, i.e., a reticulated bio-based sponge.

2. The method for preparing a porous reticular bio-based sponge by regenerating waste polyurethane foam according to claim 1, characterized in that: The polyurethane foam in step S1 is waste soft polyurethane foam and needs to be crushed into 1-5 cm before use.

3. The method for preparing a porous reticular bio-based sponge by regenerating waste polyurethane foam according to claim 1, characterized in that: In step S1, the alcoholysis agent is compounded from the following raw materials in percentage by mass: 10-25% bioethanol, 35-50% crude glycerol, 7-15% furfuryl alcohol, 15-25% 1,4-butanediol, and 8-20% polylactic acid.

4. The method for preparing a porous reticular bio-based sponge by regenerating waste polyurethane foam according to claim 1, characterized in that: The catalyst A is at least one of dimethyl bismuth, zinc acetate, 9-mesityl acridine, tetrabutyl titanate, titanium dioxide, antimony trioxide, molybdenum trioxide, and iron-based montmorillonite.

5. The method for preparing a porous reticular bio-based sponge by regenerating waste polyurethane foam according to claim 1, characterized in that: The auxiliary agent in step S2 is one of oleic acid, linoleic acid, ricinoleic acid and linolenic acid; the catalyst B is one of potassium hydroxide, sodium hydroxide, sodium ethoxide and potassium ethoxide.

6. The method for preparing a porous reticular bio-based sponge by regenerating waste polyurethane foam according to claim 1, characterized in that: The catalyst in step S3 is a delayed amine catalyst A300 and stannous octoate T9, and the mass ratio of the two is 1:1-3; the isocyanate is one of toluene diisocyanate TDI and polyphenyl polymethylene polyisocyanate PMDI.

Citation Information

Patent Citations

  • Method for acidolysis of soft polyurethane foam waste to produce polyol

    CN107286369A

  • Method for preparing PLA-PPC-PU copolymer alloy by utilizing PLA reclaimed material, and product and application of copolymer alloy

    CN112831017A

  • Method for multi-stage degradation and recovery of polyether polyol in polyurethane foam

    CN113637220A

  • Non-filler bio-based degradable polyurethane sponge and preparation method thereof

    CN113754849A

  • Process for cracking polyurethane products

    CN117480207A

Cited By

  • Recycling method and application of waste paint slag generated in powder polyester paint spraying process

    CN121609969A

  • A method for recycling waste paint residues generated in a powder polyester paint spraying process and application thereof

    CN121609969B